Pacific Matildas: Finding the Women in the History of Pacific Archaeology - Emilie Dotte-Sarout (Bulletin of the History of Archaeology, 2021)
In this paper I present the background and rationale for a new research project that aims to rediscover the first women who participated in the development of archaeology in the Pacific, from the 19th to the mid-20th century. I discuss how this research is inscribed in the history of women in science, responding to Rossiter’s plea to future scholars: to write a history and sociology of science that is more comprehensive by integrating ever more of the hidden women scientists, or ‘Matildas’. I consider how a history of these ‘Pacific Matildas’ can be connected to factors that have been identified as historically keeping women out of science (especially fieldwork-based sciences) as well as keeping them out of historical records about the making of science. After discussing the methodological and conceptual frameworks envisaged for such a project, I present some preliminary results of this research: a short overview of historical figures already identified and a brief examination of one early case-study in the history of the first women engaged in the discipline, that of Adèle de Dombasle in the mid-19th century. I conclude by highlighting what the first clues we can gather about such stories tell us both about the historical place of women in the field and the place of women in the history written about the field.